De estetiska idealens motsägelsefullhet: En explorativ kvalitativ studie kring ideal i Sverige - Bondsäter,Karin; Edström,Katarina (2025)
This study aimed to explore how aesthetic ideals in Sweden are described as a part of a larger research project about sexual satisfaction at Lund University. 450 adults answered an online survey which included a question regarding the content of society’s aesthetic ideals. We analyzed the answers with a reflexive thematic analysis with a critical realist approach. The analysis resulted in three themes from the answers of the participants: “Everything, All at Once”, “The Importance of Being Normal” and “‘No Traces from Life’”. Our study resulted in a description of aesthetic ideals in Swedish society but also an analysis of how the aesthetic ideals in Sweden are contradictory and prone to exclusion. The study contributes to the research area through describing the current aesthetic ideals and how they can be connected to norm theory. The results of the study are supported by previous research from other countries, but also research of norms and marginalization. We believe future research should focus on how to prevent the negative effects of a negative body image and how individuals can build a positive body image. The results of the study can give insight to people who experience a negative body image or to individuals who engage with people with a negative body image, whether that is professionally or interpersonally.
Keywords: body ideals; norms; reflexive thematic analysis; adult; survey; kroppsideal; normer; reflexiv tematisk analys; vuxna; enkät